Репрезентування складових, критеріїв і рівнів розвитку компетентності вчителів іноземних мов у стандартах США - Леврінц Маріанна; Lőrincz Marianna; Levrints Marianna (Глухівський національний педагогічний університет імені Олександра Довженка, 2020)
Резюме. У статті представлено результати вивчення складових, критеріїв і рівнів розвитку професійної компетентності вчителів іноземних мов у стандартах педагогічної освіти й розвитку США. Вимоги до фахової підготовки й розвитку вчителів-філологів в освітніх стандартах представлено у трьох аспектах: професійні знання, вміння і диспозиції. Порівняльний аналіз текстів стандартів різних профільних організацій виявив, що принципами їхнього укладання є спорідненість, послідовність і наступність. Основними елементами професійної компетентності є іншомовна комунікативна компетентність, методична, культурологічна, психолого-педагогічна, інформаційно-технологічна і т. ін.

Abstract. The present paper examines the standards of foreign language teacher preparation and development in the USA in the context of competence oriented educational paradigm. . The joint vision of the language teachers’ competence of the American educational researchers and practitioners is presented in the relevant standards. Standards, thus, reflect the strategic aims and expectations of language teacher education as a result of consensus reached by the country’s professionals. The comparative analysis of the standards of different professional bodies revealed several underlying principles of their development: congruence of the content of standards of different professional organizations and within the same document, as well as consecutiveness and consistency, i.e. the nature of professional preparation and development of language teachers and the accompanying qualitative changes along the continuum of competence growth are taken into account. The structure of foreign language teacher’s professional competence is made up of three main constituents: professional knowledge, skills and dispositions. Its main elements include the communicative language competence, linguistic, cultural, language teaching competence (methodological/ linguodidactic), general pedagogic and psychological, technological and some others. In the course of competence development the redistribution of focus in the structure of competence is mirrored in the analysed documents. Thus, teacher candidates should seek to improve the knowledge and skills closely related to their content area such as foreign language communicative competence (including knowledge of linguistics, language, communication), cultural, methodological competence etc. Novice teachers are expected to enhance their pedagogic and psychological competence, while experienced teachers are to aspire for professional growth, their students’ academic gains and recognize the importance of life-long learning.

Резюме. В статье представлены результаты изучения составляющих, критериев и уровней развития профессиональной компетентности учителей иностранных языков в стандартах педагогического образования и развития США. Сравнительный анализ текстов стандартов различных профильных организаций свидетельствует, что принципами их составления является родство, последовательность и преемственность. По структуре профессиональная компетентность представлена в трех аспектах: профессиональные знания, умения и диспозиции. Основными элементами профессиональной компетентности является иноязычная коммуникативная компетентность, методическая, культурологическая, психологопедагогическая, информационно-технологическая и т.д.
Representation of compositions, criteria and levels of development of foreign language teachers’ competence in US standards
Репрезентация составляющих, критериев и уровней развития компетентности учителей иностранных языков в стандартах США
https://drive.google.com/file/d/1N1RVNeSEw_mfxjB4wMSMI1UeFlgwPiOX/view
Keywords: фахова компетентність; вчитель іноземних мов; стандарти педагогічної освіти і професійного розвитку; вимоги; складові; критерії і рівні розвитку компетентності; США